Spread Spectrum Concept Applied in New Accurate Medium-Long Range Radiopositioning System - Nard, Georges (The International Hydrographic Review, 2015)
Principles of Spread Spectrum Systems (SSS) have already found several radiolocation applications well known in the field, such as Syledis, JTIDS or GPS Navstar. All these existing systems operate UHF or SHF with relative spectral widths which do not exceed 1 or 2 per cent of the frequency carrier. In the new application, subject of this paper, a far larger extension of the spectrum spread associated with a drastic narrowing of the base band useful for the radiopositioning information leads to a very high B/b0 bandwidth expansion ratio of 108 or so. This opens to the conception of a new precise (5 to 20 metres) land-based radiopositioning system which is lightweight, of high discretion, and capable of any weather long range operation (up to 1 200 kilometres). This system, named Geoloc, fully eliminates drawbacks often undergone by other existing systems such as ionospheric and multipath interferences, position or phase ambiguity and frequency allocation. Two years of prototype field experiments validate the overall concept of the system, the full compatibility with other radio services, the safety and reliability of position information offered. Either standing alone or integrated with other location means, Geoloc is a modem, precise, easy to set and move system. Its all-time, all-weather long range allows the easy coverage of extended continental shelves when the most precise and reliable positioning is required. For tomorrow this kind of system will offer either an important alternative to Global Positioning Systems or a useful complement to compensate the effects of a momentary precision shade-off or degrading, or some restriction in the use of these systems.